The evolution of pneumococcal vaccine on children in Malaysia: the efficacy and outcome - Yusuff, Semiat Opeyemi; Masri, Siti Norbaya; Dzaraly, Nurul Diana; Mohd Taib, Niazlin; Mohd Desa, Mohd Nasir (TMR Publishing Group, 2021)
With pathogenic bacterium, numerous studies have been conducted in developing new vaccines, and available pneumococcal vaccines have been implemented for the prevention of related diseases. Meanwhile, Streptococcus pneumoniae is known to have developed resistance to many of the proposed preventive measures. As a result, contemporary research, including our study, has reviewed how Streptococcus pneumoniae has become resistant to vaccines and to further determine how to prevent the negative effect of the non-vaccine serotype on vaccine serotype efficacy. Pneumococcal have been known as one of the bacteria that has highest preventive strength of vaccination provided to humans, where children’s immunity requires the vital of it, based on immunization schedule to boost their immune system against the diseases of high mortality and morbidity. All pneumococcal vaccines are derived from its strains called serotypes, and further research is being conducted to determine more potent vaccines from other pneumococcal virulence factors. To impose and implement the pneumococcal vaccine, the serotype distribution needs to be verified. To deal with this verification, clinical or carriage samples are required for the determination and differentiation of vaccine serotypes from non-vaccine serotypes. In Malaysia, the carriage rates are often limited to the clinical epidemiology of Streptococcus pneumoniae. Carriage samples are more needed in tracking the vaccine efficacy for pre- and post-immunization to prevent and reduce pneumococcal diseases before they manifest into clinical infections. Thus, in this review article, we explore the mentioned highlights for sufficient discussion, discovery, and knowledgeable implementation of pneumococcal vaccine.